2016
DOI: 10.1007/978-3-319-45507-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Cyber Risk of Insurance Customers: The Insurance Company Perspective

Abstract: Part 1: The International Cross Domain Conference (CD-ARES 2016)International audienceAs a basis for offering policy and setting tariffs, cyber-insurance carriers need to assess the cyber risk of companies. This paper explores the challenges insurance companies face in assessing cyber risk, based on literature and interviews with representatives from insurers. The interview subjects represent insurance companies offering cyber-insurance in a market where this is a new and unknown product. They have limited his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Others deal with the cybersecurity insurance companies (i.e. the suppliers of cybersecurity insurance services), mainly in the context of assessing cybersecurity risks (Eling & Schnell, 2016;Meland et al, 2017;Tøndel et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Others deal with the cybersecurity insurance companies (i.e. the suppliers of cybersecurity insurance services), mainly in the context of assessing cybersecurity risks (Eling & Schnell, 2016;Meland et al, 2017;Tøndel et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other research examined the insurance market in different geographical zones, as well as the decision process of insurance companies relating to cybersecurity insurance and risk handling. Tøndel et al (2016) emphasized the supplier, the cybersecurity insurance companies, mainly in the Nordic market, and examined their challenges in assessing cybersecurity risk. They found that the abilities of insurance companies to evaluate risk assessment is highly impacted by limited experience with cybersecurity insurance services and little historical data to rely on.…”
Section: The Cybersecurity Insurance Suppliersmentioning
confidence: 99%
See 1 more Smart Citation
“…The Norwegian cyber-insurance market has previously been investigated by Tøndel et al , who conducted interviews with a limited number of key insurance companies offering cyber-insurance on the Norwegian market in in 2015 (Tøndel et al , 2016). This differs from our study, in that no other relevant actors such as brokers were included.…”
Section: Related Workmentioning
confidence: 99%
“…Tøndel et al (2016) aimed to identify challenges and cyber-risk assessment practices of insurance companies. However, findings were scarce as companies did not give ‘any clear priorities on which risk factors they consider most important’.…”
Section: Related Workmentioning
confidence: 99%